PARÁMETROS PRODUCTIVOS DE TERNERAS HOLSTEIN FRIESIAN AL DESTETE ALIMENTADAS CON DOS CONCENTRADOS PELETIZADOS COMERCIALES EN EL ESTABLO DOÑA FRANCISCA S.A.C. - Caballero González, Aldo Antonio (2017)
This research was carried out in Doña Francisca S.A.C., located in the District of Paiján, Province of Ascope, La Libertad Department, to determine the productive parameters in Holstein Friesian heifer calves fed with two commercial pelleted concentrates. Twenty - nine calves randomly distributed in three treatments were used: T0: Stable flour concentrate, T1: commercial pelleted concentrate Criavaquina, T2: commercial pelleted concentrate Terminor Plus. The highest weight at weaning was for T1 with 78 kg, T0 with 77 kg and T2 with 71,8 kg. Significant statistical differences were found (P<0,05). The largest size at weaning was for T1 with 93,9 cm, T0 with 93,3 cm and T2 had 91,3 cm. No significant statistical differences were found (P>0,05). The greatest weight gain was for T1 with 38,6 kg, T0 with 37,8 kg and T2 with 33,3 kg. Significant statistical differences were found (P<0,05). Food intake was higher in the T0 with 36,6 kg, the T1 with 35.9 kg and the T2 had 35,2 kg. No significant statistical differences were found (P>0.05). The feed conversion was better in T1 with 0,93; T0 with 0,97 and the T2 achieved 1,12. No significant statistical differences were determined (P>0,05). T1 had the lowest percentage of diarrhea with 46%, T0 with 69% and T2 with 76%. No significant statistical differences were found (P>0,05). There was no mortality in the treatments. The cost-benefit ratio was S/.6,26 for T1, S/.6,34 for T0 and S/.7,28 for T2. It was concluded that the best productive parameters at weaning were achieved with commercial pelleted concentrate Criavaquina.